Dekonstruksi Kematian sebagai Sebuah Obsesi Modernitas: Refleksi atas Pemikiran Zygmunt Bauman - Putranto, Hendar (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2012)
Facing death is never an easy task to accomplish, not even for modernity which claims to master and understand all things under the sun. Many philosophers and thinkers ponder upon “death” as both a mystery and a problem, grand in scope and unfathomable in depth. Nevertheless, only a few thinkers relate death with modernity. Zygmunt Bauman is one of the living legends in this respect. With him, one is challenged to be unsettled on the case of thinking about the phenomenon of death and its implications within the framework of modernity’s project, obsession, critique, and power struggle. Deconstructing mortality is arguably one of modernity’s persistent obsessions. By applying hermeneutical approach, Bauman envisions three ways of modernity’s reading on the issue of mortality as well as three strategies to deal with it, namely degeneration, hygiene and immigrant. However, these three readings and strategies, though convincing and relevant in interpreting modernity’s attitude toward death, are lacking in prediction and predilection of the future. Hans Jonas’ way of dealing with mortality issue is discussed at the end of this paper to complete the philosophical reflection on death by Bauman.